Farmer's views and values to focus on cattle conservation policies: the case of eight European countries - Gandini, G.; Martin-Collado, D.; Colinet, F.; Duclos, D.; Hiemstra, S.J.; Soini, Katriina; Diaz, C. (Blackwell, 2012)
Our aim was to identify elements useful in designing policies and programmes for conservation of farm animal genetic resources, taking as case study a group of European local cattle breeds. We first investigated the implications of differences among countries in the policies and programmes to be developed. Secondly, we analysed key elements common to countries, which may affect local breed viability. We used the herd size trend expected by the farmer in the near future as an indicator of breed viability. Fifteen breeds, for a total of 355 farms, were surveyed. To take into account the multiple factors influencing breeds demographic trends, the questionnaire included economical, technical and social aspects. Among the major differences across countries was the perception of the farmer on the value attributed to the local breed by society. Concerning the elements common to countries and their association to breed viability, the greater the collaboration among farmers and the stakeholders appreciation as perceived by the farmer, the greater the viability of the farm. An opposite trend was observed for the age of the farmer. Older farmers generally planned to soon cease farming or decrease herd size, whereas young farmers planned to increase the size of their herds. Implications of including these elements in conservation polices are discussed.
Keywords: Ma; eläingeenivarat; säilyttäminen; suojelu; maanviljelijät; genetic resources; cattle; farmers; public opinion; farm animal genetic resources; local breeds; viable breeds; mielipiteet; asenteet